2018
DOI: 10.1371/journal.pone.0193381
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunctions in MS in relation to neuropsychiatric aspects and its psychological treatment: A scoping review

Abstract: ObjectiveSexual dysfunction in multiple sclerosis (MS) is a significant, but often underestimated and overlooked suffering. Interventions to treat sexual dysfunction in MS are rare. The relation between sexual dysfunction in MS and psychological as well as neuropsychological aspects is evident. However, this field of research remains markedly underdeveloped in this severe chronic illness. The aim of this scoping review is to describe the relevant knowledge in this area and to identify psychological interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 61 publications
1
34
0
1
Order By: Relevance
“…SD may however occur secondary to different neurological disabilities such as spasticity, poor mobility, pain, fatigue, inattention/poor concentration, bladder/bowel incontinence, or at a tertiary level from the sociocultural, emotional, and psychological consequences of MS. Sexual dysfunction is related to mood disorders, diminished self‐esteem, impaired body image, and also to psychological aspects of the relationship with the partner …”
Section: Introductionmentioning
confidence: 99%
“…SD may however occur secondary to different neurological disabilities such as spasticity, poor mobility, pain, fatigue, inattention/poor concentration, bladder/bowel incontinence, or at a tertiary level from the sociocultural, emotional, and psychological consequences of MS. Sexual dysfunction is related to mood disorders, diminished self‐esteem, impaired body image, and also to psychological aspects of the relationship with the partner …”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature concluded that there is an urgent need for the development and adequate evaluation of psychological interventions for sexual dysfunctions in MS. The authors suggest that sexual dysfunction and its impact on psychological health should be more focused in practice [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This autoimmune disease is characterized by a variety of unpredictable signs and symptoms, such as muscle cramps, fatigue, pain, visual disturbances, dysphagia, speech and breathing disorders, bladder and intestinal problems, cognitive disorders, and sexual problems [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunction (SD) is an important public health concern and a common symptom in MS patients, with a prevalence of 40% to 80% [9,10]. Previous studies have suggested the incidence rate of SD to be 31% among Iranian females, but the prevalence of SD in Iranian women with MS is unknown [11].…”
Section: Introductionmentioning
confidence: 99%